Expanded hemodialysis: new opportunities and hopes - L. Surzhko (Український Журнал Нефрології та Діалізу, 2020)
In the field of hemodialysis technologies, as in other fields of medicine, evolutionary changes are constantly taking place. The innovations are driven by unachieved clinical outcomes and desire to improve the quality of care of patients with CKD 5D. Recent advances in dialysis techniques resulted in the possibility to expand the permeability of dialysis membranes for a wider spectrum of uremic toxins that lead to the enhancement of long-term outcomes improving quality of life and reducing the mortality rate of dialysis patients. The inadequacy of existent dialysis techniques, at least in part, is due to the chronic accumulation of organic retention solutes of middle and large molecules, which are poorly or even not removed during dialysis.